AN ASSESSMENT OF MOTIVATIONAL FACTORS INFLUENCING EMPLOYEE PERFORMANCE IN DEVOLVED GOVERNMENTS IN KENYA: A CASE OF WAJIR COUNTY - Jehow, Fatuma Abdi; Gikandi, Dr. Joyce; Mwencha, Dr. Peter M (European Journal of Business and Strategic Management, 2018)
Purpose: The main purpose of this study was to examine the motivational factors influencing employee's performance in Wajir County, Kenya. Methodology: The study employed descriptive survey design and the target population of the study was 153 senior, middle and lower level managers at Wajir county Government. The stratified random sampling method was used in selecting the respondents in all the thirteen departments. The sample size was 111. The study used questionnaires to collect the required data. Descriptive statistics was used mainly to summarize the data. SPSS was used for analysing complex data. Data presentation was through the use of pie charts, bar charts, graphs and frequency tables. Regression and Correlation analysis was used to establish the relationship between the independent and dependent variables. Results: The study found out that staff motivation at Wajir County was at moderate level and among the strategies that the county had on staff motivation included: promotions training and performance appraisal; allowances (overtime allowances); advisory services and certificate of performance and special recognition during meetings. the study established that training and development improved employees' skills and knowledge hence more production; it created job satisfaction and the county would be able to retain the qualified employees it employed and it improved performance thus achievement of targets. Policy recommendation: The study recommended that the County Government of Wajir should create and execute clear workers training and advancement programs that are worker headed to permit staff procure the essential aptitudes and map out their vocation improvement plan which thus positively affects worker performance. The County ought to likewise guarantee that worker inspiration is natured in an association by making a favorable workplace, arrangement of clear sets of responsibilities, and additionally guaranteeing convenient input is given to representatives on issues addressing work Performance.